Peningkatan Literasi Membaca Melalui Penerapan Metode Membaca Kontesktual Pada Siswa Kelas X1 SMA Negeri 2 Kota Kupang Tahun Pelajaran 2024/2025: Indonesia - Feby Meriyana Atto; Sanhedri Boimau; Richard Oematan (Ciencias : Jurnal Penelitian dan Pengembangan Pendidikan, 2026)
This study aims to determine the improvement of reading literacy through the application of contextual reading methods in class X1 students of SMA Negeri 2 Kota Kupang in the 2024/2025 academic year. This type of research uses classroom action research (PTK), by going through several stages, namely: planning, implementation, observation and reflection. The subjects of this study were 30 students of class X1 SMA Negeri 2 Kota Kupang. Data were collected using observation, test and documentation techniques. The results of this study showed that out of 30 students in Cycle I and Cycle II that the application of contextual reading methods can improve students' reading literacy.